Auditoría interna al recurso humano en una institución de educación superior. - Vargas Quinchia, Lady Juliana (Universidad Antonio Nariño, 2024)
In this new reality where companies have been forced to reinvent themselves and find ways that adapt to the needs of their businesses; Human resources, as a fundamental piece, require a work environment that motivates and generates empathy in the processes they carry out.